An enquiry into citizenship education curriculum and pedagogy: the role of technology and student voice - Olla, Venus (2013)
The research in this thesis explores Citizenship Education pedagogy at secondary school level in Ontario, Canada. Citizenship Education is a complex subject area and its teaching and learning within the classroom is contentious. The literature indicates the value of student voice and technology; however the ways in which these pedagogical tools can be incorporated into the Citizenship Education classroom have not been explored in great detail.